Lokale organisasjoner uten en nasjonal overbygning: Brannkassene 1816–1914 - Harald Espeli (Heimen)
Abstract This article analyses the establishment and successful diffusion of fire insurance mutuals in the Norwegian countryside between 1816 and World War I. Prior to the establishment of fire insurance mutuals, the only means of fire insurance of farm houses and farm outbuildings for Norwegian peasants and farmers was the state fire insurance company, Norges Brannkasse. Although the Norwegian fire insurance market was the most open in Europe, foreign insurance companies restricted themselves to insurance of chattels and stocks. However, their premiums were too expensive for peasants and farmers, who developed local fire insurance mutuals based on apportioned liability. They were mostly run by unpaid or symbolically remunerated elected representatives creating small administrative costs. The fire insurance mutuals also proved effective in coping with the challenges of moral hazard and asymmetric information. Thus, fire damages were lower than in Norges Brannkasse. From 1890s the fire insurance mutuals insured larger values than Norges Brannkasse in the countryside. Thus, the fire insurance mutuals played an important role in the economic modernization of the countryside until World War I.